The influence of using fintech P2P Lending and QRIS on MSME performance with e-commerce as an intervening variable - Driana, Thasania Fitri; Soma, Abdul Mukti; Sitorus, Palti Marulitua (ARKA INSTITUTE, 2025)
The growth of Financial Technology (Fintech) in Indonesia, particularly Peer-to-Peer (P2P) lending services, has significantly impacted financing access for Small and Medium Enterprises (SMEs) by facilitating loans through digital platforms. This serves as a vital alternative amid traditional financial constraints, promoting the development of Microfinance Institutions (MFIs). Concurrently, e-commerce transformation and Quick Response Code Indonesian Standard (QRIS) implementation have accelerated digital economy growth, enabling SMEs to expand their businesses and reach broader markets. Nonetheless, challenges such as enhanced governance, risk management, and regulatory adaptation remain crucial for supporting sustainable SME growth. This study investigates the effect of P2P Lending and QRIS on SME performance via e-commerce in Bandung City. Using quantitative research methods and a Likert scale, the study surveyed a population of 523,584 SMEs, targeting 300 respondents. Data analysis was conducted using Structural Equation Modeling (SEM) with SmartPLS. Results indicate a significant impact of P2P Lending and QRIS on SME performance through e-commerce, with P2P Lending contributing an influence of 0.109, QRIS 0.121, and e-commerce 0.329. These findings aim to enhance understanding of how P2P Lending and QRIS affect SME performance via e-commerce.